URGENSI PENGATURAN NOTARIS DAN PEJABAT PEMBUAT AKTA TANAH SEBAGAI PIHAK PELAPOR ATAS TRANSAKSI KEUANGAN MENCURIGAKAN TERKAIT TINDAK PIDANA PENCUCIAN UANG - Made Riyaldi (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract One mode of money laundering is often used of late is the buying and selling of land and or building/real estate. By langusng or indirectly this mode involves a notary and PPAT as officials make the authentic deed of sale and purchase of real estate subject. One of the factors that cause the mode of money laundering by using this lively real estate is not dikategorikannya the notary and PPAT as the rapporteur in the money laundering Act. Thus, it appears the problem about: How did the concept of notary and PPAT settings as the rapporteur over suspicious financial transactions related to money laundering criminal offence in law PPTPPU?